Ray to go : a communication campaign to encourage proper UV protection habits in Singapore - Lim, Aurelia Ying Yi (2019)
Ray to Go is the first holistic UV protection campaign in Singapore that delves into an in-depth understanding of UV protection for both skin and eyes. It aims to educate women aged 25-35 to adopt proper, daily UV protection behaviours by integrating them into existing self-care routines. Ray to Go was conceptualized and executed as the final year project by four final-year undergraduates from the Nanyang Technological University Wee Kim Wee School of Communication and Information. The campaign was born out of a recognition of the commercialization and trivialization of the health issues surrounding UV damage. Against the background of Singapore's high UV index, all year round, most campaigns and insights on the cause were commercialised and oversimplified. With the lack of local literature and comprehensive campaigns, a glaring gap was identified. Partnering key industry experts in the field of optometry and dermatology, the team took to extracting the social cause from the pertinent and relevant issue of UV protection in the local landscape, employed lifestyle and niche marketing to promote UV protection as a daily routine. A highlight is the creative aspect of the campaign event, ‘Way to Glow', that promoted the cause through subtle but highly targeted messaging through small-scale, intimate workshops. The campaign was successful in reaching out to its specific target group and received the support of prominent lifestyle media titles in covering and shedding light on the project. Efforts from this campaign also resulted in a notable behavioural change in the target audience.